(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
The formation of patriotism is one of the priorities in the field of Secondary Education. Traditionally associated with the increase in the civil-patriotic, spiritual moral, legal and psychological mining of most social institutions that carry out socialization. Introducing patriotism to the level of self-awareness, social activity, Uzbek cultural historical values and Customs is one of the main most important tasks in increasing the patriotic sense of youth. The article is based on a problematic approach to the formation of youth patriotism. Their patriotic directions, values are analyzed. The state, problems and factors of the formation of youth patriotism are considered.